Comparison of Candida species in patients with Candida vulvovaginitis in Torbat-e Jam and its relationship with diabetes - Parisa Barmar; Hossein Zarrinfar; Lida Jarahi; Abdolmajid Fata (Mashhad University of Medical Sciences, 2021)
Introduction: Candida vulvovaginitis is one of the most common vaginal infections in women and in women with diabetes. Although C. albicans has been reported to be the most common cause of this infection, but there have been recent changes in the pattern of Candida causing Candida vulvovaginitis. This study was performed with aim to investigate the frequency of dominant Candida isolates in patients with Candida vulvovaginitis in Torbat-e Jam and its relationship with diabetes. Methods: In this cross-sectional study, 428 women with suspected Candida vulvovaginitis referred to Torbat-e-Jam medical centers were assessed in 2019. Two specimens of vaginal secretions were taken from each patient. The first specimen was cultured on sabouraud dextrose agar (SDA) medium, and the second one was directly examined using wet mount microscopy. The Candida colonies were passaged on CHROMagar Candida medium to identify the species. Demographic and diabetes characteristics of the patients were evaluated. Data were analyzed by SPSS software (version 16) and Chi-square test. p<0.05 was considered statistically significant. Results: 309 positive yeast cultures were obtained from the patients with Candida vulvovaginitis. Identified Candida species included: 145 (46.9%) C. albicans, 53 (17.2%) C. glabrata, 45 (14.5%) C. parapsilosis, 33 (10.7%) C. krusei, and 33 (10.7%) C. tropicalis. Forty-one specimens (13.3%) also had two types of Candida species. Forty-one patients (13.3%) affected to Candida vulvovaginitis also had diabetes that no significant relationship was observed. Conclusion: The frequency of non-albicans Candida is relatively higher than C. albicans in patients with Candida vulvovaginitis in Torbat-e Jam, and C. glabrata is the most common among non-albicans species. The incidence of Candida vulvovaginitis was not significant in patients with diabetes. C. parapsilosis was most common among non-albicans species in diabetics patients.